(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the main problems faced by women in the southern regions of Uzbekistan in maintaining their health. The socio-economic conditions of the region, the quality of medical services, women’s knowledge and skills regarding a healthy lifestyle, early marriages, reproductive health, and practical situations in the protection of motherhood and childhood are highlighted. Factors such as the lack of medical infrastructure, the level of gender equality, the impact of the environmental environment, and the legal and social activity of women are considered as factors affecting the effectiveness of the health care system. Proposals and recommendations aimed at eliminating these problems are also presented.